Does Fit Matter? The Impact of Task-Technology Fit and Appropriation on Team Performance in Repeated Tasks - Fuller, Robert M.; Dennis, Alan R. (Information Systems Research, 2009)
Prior research on technology and team performance concludes that the fit of the technology to tasks influences team performance. It also suggests that the way teams appropriate technology influences performance. This research examines how fit and appropriation (from the Fit Appropriation Model) influence performance over time. Initially, the results show that fit better predicted performance; teams using poor-fitting technology performed worse than teams with better fitting technology. However, over a short time period (two days in this study), this initial fit no longer predicted performance; performance of teams using better fitting technology remained constant while teams using poor-fitting technology innovated and adapted, improving performance. There are two key findings from this study. First, fit can predict team performance soon after technology adoption, but initial assessments of fit are temporary as teams innovate and adapt; thus, our current theoretical models of fitting technology to a task likely will not be useful beyond the first use. Second, teams should understand how to better adapt existing technology and work structures. Because our current theories of task-technology fit failed to predict performance beyond the first use of technology, we believe that this calls for a reconsideration of what fit means for teams using technology.